2003
DOI: 10.1038/nm881
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced T-cell immunogenicity of plasmid DNA vaccines boosted by recombinant modified vaccinia virus Ankara in humans

Abstract: In animals, effective immune responses against malignancies and against several infectious pathogens, including malaria, are mediated by T cells. Here we show that a heterologous prime-boost vaccination regime of DNA either intramuscularly or epidermally, followed by intradermal recombinant modified vaccinia virus Ankara (MVA), induces high frequencies of interferon (IFN)-gamma-secreting, antigen-specific T-cell responses in humans to a pre-erythrocytic malaria antigen, thrombospondin-related adhesion protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
414
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(441 citation statements)
references
References 43 publications
23
414
4
Order By: Relevance
“…We and others demonstrated multi-specific multifunctional T cell responses induced by the DNA-rMVA regimen in NHP (here and [3,37,38]), again similar to results in humans, with the exception that human responses were biased towards the CD4 + T cell compartment [27,[39][40][41]. This CD4 + T cell bias might be due to differences in the relative vaccine doses used in NHP compared to those used in humans.…”
Section: Discussionsupporting
confidence: 76%
“…We and others demonstrated multi-specific multifunctional T cell responses induced by the DNA-rMVA regimen in NHP (here and [3,37,38]), again similar to results in humans, with the exception that human responses were biased towards the CD4 + T cell compartment [27,[39][40][41]. This CD4 + T cell bias might be due to differences in the relative vaccine doses used in NHP compared to those used in humans.…”
Section: Discussionsupporting
confidence: 76%
“…Here, we have shown that these augmented responses were directed not only at epitopes known to be frequently targeted by HIV-1-infected persons but also new epitopes that were also recognised by HIV-uninfected subjects given this vaccine [24,25]. While there is now substantial evidence that MVAvectored vaccines expressing antigens from pathogens other than HIV-1 can efficiently expand primed CD4 + T cells in HIV-uninfected human subjects [25,34,35], our data suggest that MVA.HIVA vaccination can stimulate HIV-1-specific T helper responses to a greater array of epitopes than those targeted by CD4 + T cells during chronic infection. In contrast, in earlier studies involving therapeutic vaccinations with an MVA vaccine expressing the HIV-1 nef gene, cellular responses to nef epitopes were boosted by immunisation but generated conflicting results with regard to amplification of T helper responses [36,37].…”
Section: Discussionmentioning
confidence: 88%
“…Because of differences in HLA types and epitope recognition over the course of infection, whole viral proteins may be more effective components of an HCMV vaccine than selected viral epitopes. The attenuated poxviruses used to detect HCMV-specific CD8 ϩ T cells have been used successfully to generate immune responses against HIV and malaria (64,65). The appeal of these viruses is demonstrated safety and lack of virulence in vulnerable populations such as adolescents and the elderly (66,67).…”
Section: Discussionmentioning
confidence: 99%